2001
DOI: 10.1038/88404
|View full text |Cite
|
Sign up to set email alerts
|

A use-dependent tyrosine dephosphorylation of NMDA receptors is independent of ion flux

Abstract: Tyrosine phosphorylation can upregulate NMDA receptor activity during pathological and physiological alterations of synaptic strength. Here we describe downregulation of recombinant NR1/2A receptors by tyrosine dephosphorylation that requires agonist binding, but is independent of ion flux. The tyrosine residues involved in this new form of NMDA receptor modulation likely form a 'ring' adjacent to the last transmembrane domain. The downregulation was due to a reduction in the number of functional channels, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
223
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(233 citation statements)
references
References 49 publications
7
223
0
Order By: Relevance
“…Several mechanisms have been proposed for the regulation of NMDAR functions, including altering the phosphorylation state and biophysical properties of the channel (47,48) and changing NMDAR trafficking and channel numbers at the membrane (49,50). Our previous finding suggests that 5-HT 1A decreases surface NR2B clusters in a microtubule-dependent manner (21), consistent with the role of cytoskeleton-based transport on NMDAR insertion to the plasma membrane (51,52).…”
Section: Discussionsupporting
confidence: 64%
“…Several mechanisms have been proposed for the regulation of NMDAR functions, including altering the phosphorylation state and biophysical properties of the channel (47,48) and changing NMDAR trafficking and channel numbers at the membrane (49,50). Our previous finding suggests that 5-HT 1A decreases surface NR2B clusters in a microtubule-dependent manner (21), consistent with the role of cytoskeleton-based transport on NMDAR insertion to the plasma membrane (51,52).…”
Section: Discussionsupporting
confidence: 64%
“…To test whether clathrin-dependent endocytosis of NMDA receptors (Vissel et al, 2001;Nong et al, 2003) is also involved in the 5-HT 1A modulation of NMDAR currents, we dialyzed neurons with a dynamin inhibitory peptide that interferes with the binding of amphiphysin with dynamin and therefore prevents endocytosis through clathrin-coated pits (Grabs et al, 1997;Marks and McMahon, 1998). We found that the effect of 8-OH-DPAT was intact in neurons loaded with the dynamin inhibitory peptide (50 M; 21.5 Ϯ 2.1%; n ϭ 4) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence has suggested that the NMDA receptor is not a static resident in the plasma membrane and may undergo regulated transport to and from the cell surface and lateral diffusion at synaptic and extrasynaptic sites in the plasma membrane (Wenthold et al, 2003;Collingridge et al, 2004). Several mechanisms have been proposed to be important for stabilizing and/or promoting surface NMDA receptor expression, including the PDZ (PSD-95/ Discs large/zona occludens-1) domain-mediated interactions between NR2 subunits and the synaptic scaffolding protein PSD-95 that is regulated by activity-dependent phosphorylation (Roche et al, 2001;Chung et al, 2004;Lin et al, 2004) and tyrosine dephosphorylation of NR1/2A receptors that triggers clathrindependent endocytosis (Vissel et al, 2001). Moreover, it has been found that NR2A and NR2B have distinct endocytic motifs and endocytic sorting, with NR2B undergoing more robust endocytosis than NR2A in mature cultures (Lavezzari et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, NR1 was not observed to be involved in neuronal protection and neurite outgrowth in the absence of LPS treatment, which may induce not only NR1 expression but also posttranslational modifications such as phosphorylation that modify its function or other factors affected in the presence of LPS (Caudle et al, 2005). Furthermore, the protective effects of NR1 may be activity dependent because membrane depolarization was required to activate NMDAR (Vissel et al, 2001). In addition, a recent study indicated that NR1 interacts with synaptic adhesion-like molecules (SALMs) and is involved in neurite outgrowth (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%